2009
DOI: 10.1152/ajprenal.00200.2009
|View full text |Cite
|
Sign up to set email alerts
|

Decreased abundance of urinary exosomal aquaporin-1 in renal ischemia-reperfusion injury

Abstract: Urinary exosomes, secreted into urine from renal epithelial cells, are known to contain many types of renal functional membrane proteins. Here, we studied whether renal ischemia-reperfusion (I/R) affects urinary exosomal aquaporin-1 (AQP1) excretion in rats subjected to renal I/R and patients who underwent renal transplantation. Immunoblotting studies demonstrated reduction of the urinary exosomal AQP1 level even at 6 h after renal I/R, and the level continued to be low over 96 h after I/R. Renal AQP1 mRNA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
110
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 27 publications
7
110
0
Order By: Relevance
“…Urinary exosomes, on the other hand, are derived from the kidney and mostly contain proteins secreted by the kidney tissue. Based on this rationale, several recent papers have reported potential new markers of kidney disease in urinary exosomes [1][2][3][4] . However, there is still lack of experimental confirmation that urinary exosomes indeed represent changes in the kidney tissue, which may not be detectable in whole urine.…”
mentioning
confidence: 99%
“…Urinary exosomes, on the other hand, are derived from the kidney and mostly contain proteins secreted by the kidney tissue. Based on this rationale, several recent papers have reported potential new markers of kidney disease in urinary exosomes [1][2][3][4] . However, there is still lack of experimental confirmation that urinary exosomes indeed represent changes in the kidney tissue, which may not be detectable in whole urine.…”
mentioning
confidence: 99%
“…Recently, Rutkovskiy et al showed that hyperosmolarity increased myocardial AQP1 mRNA and protein glycosylation, but did not influence the total AQP1 protein (28). An isolated change in AQP1 glycosylation in the kidney was also recently reported by Sonoda et al (29). However, until now the functional significance of AQP1 glycosylation has not been conclusively determined.…”
Section: Discussionmentioning
confidence: 89%
“…8 Renal cell carcinomas have been found to shed particularly high numbers of exosomes. 9 It seems plausible-and proven in the case of AQP1-that these exosomes contain AQP1 and ADFP.…”
mentioning
confidence: 97%